Insights into the X-shaped fissure propagation and interaction mechanisms of rock specimens: 3D printing experiments and DEM simulations - Yiqing Sun; Wei Huang; Lei Gan; Zhenzhong Shen; Hongwei Zhang; Wenbing Zhang (Case Studies in Construction Materials)
X-shaped fissures are prevalent in natural rocks and significantly influence rock mass stability, yet their interaction and propagation mechanisms remain inadequately studied. This research fabricated rock-like specimens with single and double X-shaped fissures using sand 3D printing technology. Uniaxial compression tests were conducted, and the crack propagation process was analyzed via the DIC method. DEM simulations were also performed to explore the fracture mechanisms. In single X-shaped fissure specimens, crack growth is affected by the inclination angle, with Wing crack (WC) being a dominant propagation mode, and Anti-wing crack (AWC) emerging as the angle increases. In double X-shaped fissure specimens, complex fissure interactions lead to intricate crack propagation, forming through-going main cracks and elaborate crack networks, with Interaction crack (IC) being a notable feature. The stress-strain curves vary with fissure configurations. Specimens with difficult crack propagation generally have higher strength. These findings enhance the understanding of X-shaped fissure fracture mechanisms and offer crucial references for rock engineering design, construction, and stable operation.